Pengaruh Pembiayaan yang Disalurkan, Dana Pihak Ketiga, dan Jumlah Kantor Perbankan Syariah terhadap Pemulihan Ekonomi di Masa Pandemi - Aprilya Dara Dinanti; Endang Hatma Juniwati; Noorsyah Adi Noeridha (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The COVID-19 pandemic has reduced Indonesia's economic performance. The government implemented the Indonesian Economic Recovery program which was distributed to parties affected by the pandemic. One of these parties is Islamic banking. This research was conducted to determine the effect of Financing Disbursed by Islamic Banking, Islamic Banking Third Party Funds (DPK), and the Number of Islamic Bank Offices, the Covid-19 pandemic, and the National onomic Recovery Program on the Indonesian Economy as measured by real GDP. This research is a quantitative research with a descriptive approach. The population of this study is GDP and Indonesian Islamic Banking. This research was conducted using multiple linear regression analysis with dummy variables supported by Eviews 10 software for data processing. The results of this study indicate that PYD Islamic Banking has an influence on Indonesia's economic growth. The DPK and Number of Offices variables had no effect on Indonesia's economic growth during the pandemic, as well as during the implementation of the Economics Recovery Program. Keywords: GDP; Third-Party Funds; Sharia Financing; Bank Office; COVID-19; National Economic Recovery Program